Correction of artifacts in optoacoustic imaging using an iterative approach - Рудницький, О. Г.; Рудницька, М. О.; Ткаченко, Л. В. (Київський національний університет імені Тараса Шевченка, 2021)
Optoacoustic tomography is effective in applying to the visualization of objects that have a high coefficient of light absorption relative to the environment. Such tasks include, for example, defectoscopy, vascular imaging, detection and monitoring of tumors, diagnosis of porosity of composite materials, high-precision local measurement of the modulus of elasticity. However, the quality of optoacoustic images largely depends on factors such as noise (equipment or environmental noise) and distortion due to the characteristics of the model and the calculation algorithm. The article proposes an iterative algorithm for improving the quality of optoacoustic images, based on the observation that artifacts increase in magnitude with each iteration, while the nature and location of the distortions remain unchanged. Numerical simulations of the propagation of ultrasonic waves in environments close to soft biological tissues have been performed. In terms of eliminating distortion and artefacts inherent to the method of image reconstruction, an iterative filter was found to be highly effective The effectiveness of the approach is manifested in the use of a small number of iterations. Pages of the article in the issue: 98 - 107 Language of the article: Ukrainian
Keywords: optoacoustics; numerical simulation; k-Wave toolbox; оптоакустика; чисельне моделювання; k-Wave toolbox